Studi Kesukaan Panelis Terhadap Tempe dari Biji Lotus (Nelumbo nucifera) dan Kedelai (Glycine max) - Mairili Yana Sarti; Sherly Ridhowati; Shanti Dwita Lestari; Rinto Rinto; Wulandari Wulandari (Jurnal FishtecH, 2019)
This study aims to determine whether tempeh from lotus seeds can be accepted by panellist  through hedonic tests and hedonic quality. This research method uses a randomized block design (RCBD) with different proportions of lotus seeds as a treatment and repeated 3 times. Treatment with different proportions of lotus seeds is A0 (100% soybean seeds), A1 (50% soybean seeds-50% lotus seeds) and A2 (100% lotus seeds). The parameters of this study include sensory analysis of hedonic and hedonic quality (appearance, color, texture, aroma and taste). The hedonic quality sensory results significantly affect the appearance, texture, aroma and color while the hedonic effect significantly on the color but not significantly affect the taste, texture and aroma parameters. Tempe with the proportion of lotus seeds were as much as 50% better than 100% lotus seed tempeh, both of the characteristics of the quality of hedonic and hedonic.